(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Climate change is one of the major environmental challenges that adversely impact the agriculture. This paper makes a meaningful attempt to assess the effect of climate change on Indian agricultural. The temperature of The earth increases in carbon dioxide concentration, a greenhouse (GHG), are due primarily to fossil fuel use such as coal, oil and natural gases and land use change, while those of methane and nitrous oxide are primarily due to agriculture. Many manmade activities such as industrialization, urbanization, deforestation increase GHGs. Indian agriculture depends on high monsoon about, 23rd area, close link between climate and water resources and agriculture increases greenhouse gases and change climate. Then emerging many issues increasing population, high demand for food, increasing urbanization, increasing competition for recourses, increasing globalization, removal of trade barriers and new technology. Negative impacts on Indian agriculture are high rainfall, erosion top soil, rise sea level and loss of farm land due to overburden. Increasing temperature decreases crop productivity and other issues. Positive impact of Indian culture agriculture reduced frequency of frost damage, less damage to potato, peas and mustard and crops form new flood areas may become available for aquaculture regions.